Cohort profile: Korean Urban Rural Elderly (KURE) study, a prospective cohort on ageing and health in Korea. Issue 10 (16th October 2019) - Hong, Namki; Kim, Kwang-Joon; Lee, Su Jin; Kim, Chang Oh; Kim, Hyeon Chang; Rhee, Yumie; Youm, Yoosik; Choi, Jin-Young; Park, Hyun-Young
Abstract : Purpose: The Korean Urban Rural Elderly (KURE) cohort was initiated to study the epidemiologic characteristics, physical performance, laboratory and imaging biomarkers and incidence of age-related diseases in an elderly population with respect to both clinical and social aspects to develop preventive and therapeutic strategies for combatting age-related diseases. Participants: A total of 3517 adults aged 65 or older participated in the cohort at baseline from 2012 to 2015, recruited from three urban districts and one rural district in Korea. The second-wave follow-up survey is now being conducted at a 4-year interval from baseline (2016–2019; follow-up rate 71.5%). The data set included detailed information on anthropometric and socioeconomic factors, functional assessments, image scans (plain radiography, dual-energy X-ray absorptiometry and CT), biospecimens (ie, serum, urine and DNA) and social support networks along with the feasibility of linkage to a national claims database. Findings to date: Mean age of participants at entry was 71.9±4.6 years and 67% were women. From the KURE participants enrolled in baseline recruitment, several studies were published in the fields of cardiometabolic diseases, musculoskeletal health and the association between social support network and diseases in ageing. Future plans: Participants will be observed actively and passively every 4–5 years and the first follow-up will be completed in 2020. The KURE data set has strength in comprehensive physical function assessments, quantifiable imaging data sets using CT and detailed information regarding the social support networks of participants from a large community-based elderly Korean population.